Preach! (Practice not Included): A Qualified Defense of Hypocrisy. - Santana, Carlos (Ethical Theory & Moral Practice, 2024)
Hypocrisy is generally treated as particularly repugnant, perhaps the "only unforgivable sin." I argue that this attitude is misplaced. Hypocrisy—especially quotidian hypocrisy by the average citizen—plays an essential role in maintaining and promoting a good society. Hypocrisy facilitates the establishment and maintenance of beneficial social norms, and can secure better social outcomes when full compliance with a norm is suboptimal. The hypocrite then, is sometimes playing a crucial role in society, and in such cases doesn't deserve the full measure of the reprobation we usually reserve for them. Instead of focusing our reactions on their hypocrisy, we should instead target our attitudes on the misbehavior itself.